(untitled) (Contemporary Journal of Social Science Review, 2025)
In the high-pressure world of university life, romantic relationship conflicts can quietly erode students’ mental well-being, self-esteem, and academic success. This study investigated the relationship between study variables as well as examined the predictive role of romantic relationship conflict in psychological well-being, self-esteem, and academic performance among university students. A convenience sample of 200 students participated in a cross-sectional, quantitative research design utilizing standardized measures: the Romantic Partner Conflict Scale (RPCS), the Rosenberg Self-Esteem Scale (RSES), Ryff’s Psychological Well-being Scale (PWS), and the Academic Performance Scale (APS). Correlational analysis revealed that romantic relationship conflict was significantly negatively correlated with self-esteem, psychological well-being, and academic performance. Additionally, self-esteem was positively associated with both psychological well-being and academic performance, while psychological well-being also showed a modest positive correlation with academic outcomes. Regression analyses confirmed that romantic conflict significantly predicted reductions in psychological well-being, self-esteem, and academic performance. These findings highlight the detrimental impact of relationship conflict on students’ mental health and academic functioning, emphasizing the need for supportive interventions that promote healthy interpersonal dynamics during emerging adulthood.